DESERT WARRIOR - MacKie, Anthony; Copley, Sharlto; Kingsley, Ben; Hart, Aiysha (Vertical Entertainment, 2026)
An honorable and mysterious rogue, known as Hanzala, makes himself an enemy of the Emperor Kisra after he helps a fugitive king and princess in the desert.